Presupuesto por resultados y su incidencia en la gestión institucional de la municipalidad distrital de La Cuesta, periodo 2017 – 2018 - Veneros Romero, Kelly Yosmahira (2020)
Our country faces various kind of development problems and difficulties, such as the existence of isolated localities that do not have the relevant basic services, cases of extreme poverty, anemia, etc; those that hinder the integral development of its inhabitants, that is why it was decided to investigate “how the budget for results has affected the institutional management of the District Municipality of La Cuesta during the years 2017 and 2018”, because the state has been implementing this new way of budgeting since 2007 and this town has the deficiencies reported at the beginning. This research has as population and sample the District Municipality of La Cuesta, and the type of research used is descriptive, because only analyzed and interpreted the information provided by the municipality and that obtained from the “Economic Transparency Portal (Friendly Consultation) of the Ministry of Economy and Finance” without explaining the reason why or how the information occurred. Fnally, it is concluded that the budget for results had a positive impact on the institutional management of the District Municipality of La Cuesta during the periods 2017 and 2018, however it had a better impact in 2017 than in 2018.